ANALYSIS OF SEDIMENT ORGANIC CONTENT AND MACROZOOBENTHOS ABUNDANCE IN THE ESTUARY OF BATANG ARAU RIVER PADANG CITY WEST SUMATERA PROVINCE - Ridowan Kolif; Bintal Amin; Syahril Nedi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April 2017 by taking samples of sediment and macrozoobenthos from Estuary of Batang Arau River of Padang City, West Sumatera Province. The aim of the study was to analyze the content of organic sediment and macrozoobenthos abundance and the relationship of organic sediment with macrozoobenthos abundance. The method used is a survey method consisting of 4 stations with 3 replications at each station. The results showed that the average content of organic sediment material in Estuary of Batang Arau River is 10.78% and the content of organic sediment material between different stations is significantly different (P<0.01) while the abundance of macrozoobenthos is 12 ind/m2 and the abundance of macrozoobenthos between stations is not significantly different (P>0.05). The content of organic sediment material and macrozoobenthos abundance showed a weak positive relationship with the regression equation Y = 7.024 + 0.461X.Keywords: Organic Material, Abundance, Macrozoobenthos, Estuary, Pollution